Clinical assortment of preeclampsia in women with diabetes mellitus type 1 during early pregnancy: an investigative analysis - Khalid, Arfa; Akhter, Bilqees; Yazdani, Tehreem; Zohra, Sadaf; Chohan, Shazia Firdos (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the clinical predictors of preeclampsia in T1DM women during first trimester. Study Design: Cross-sectional study Place and Duration of Study: Gynaecology and Obstetrics Department of Pakistan Emirates Military Hospital, Rawalpindi, Pakistan, from Dec 2022 to Oct 2023. Methodology: A cross sectional study of 245 T1DM women was conducted in this group. Two categories of women were identified: normal (n=221) and PE (n=24). Clinical data were gathered in the first trimester, and the eGDR, (mg/kg/min) was used to quantify insulin resistance (IR) in the first trimester. Statistical analysis was done to look for variables linked to PE. Results: Preeclampsia was diagnosed in primiparae. The greatest predictor of PE was vasculopathy (OR 28.15 95% CI 8.0-98.6, p=<0.0001), followed by the duration of diabetes (25 years). PE was linked to a higher gestational weight gain (GWG) of 14 kg. Blood pressure factors of PE included both diastolic and systolic readings. PE and glycated haemoglobin (HbA1c) levels (7.5; 6.2–8.6) were substantially correlated. eGDR and PE had a negative correlation (8.6(6.6–10.6)). Triglycerides (TG) (0.94(0.6– 1.2)) were the lipids that showed a positive correlation with PE, and this correlation was true regardless of HbA1c levels. Conclusion: In T1DM women, primiparity and vasculopathy were the most significant risk factors for PE. Higher GWG was also linked to PE. PE was linked to increased TG and HbA1c levels. More research is necessary to determine the relationship between IR and PE.